2015
DOI: 10.1080/19476337.2014.998291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean oil emulsified and unemulsified with chicken plasma protein on the physicochemical properties of frankfurters

Abstract: View related articles View Crossmark data Citing articles: 8 View citing articles Effect of soybean oil emulsified and unemulsified with chicken plasma protein on the physicochemical properties of frankfurters Efecto del aceite de soja emulsionado y no emulsionado con proteína plásmica de pollo en las propiedades fisicoquímicas de las salchichas frankfurt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
6
7
0
Order By: Relevance
“…Fat content was reduced significantly with the increase of CPOE replacement and it was not significantly different at the same fat level. This trend was in line with other literature which reported the replacing of pork back fat with pre‐emulsified soybean oil could significantly reduce the fat content in sausages (Chen et al., ; Hu et al., ). Protein content was lower in reduced‐fat batches compared with the control, but there was no significant difference among all treatments as the lean meat content was kept fixed.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Fat content was reduced significantly with the increase of CPOE replacement and it was not significantly different at the same fat level. This trend was in line with other literature which reported the replacing of pork back fat with pre‐emulsified soybean oil could significantly reduce the fat content in sausages (Chen et al., ; Hu et al., ). Protein content was lower in reduced‐fat batches compared with the control, but there was no significant difference among all treatments as the lean meat content was kept fixed.…”
Section: Resultssupporting
confidence: 92%
“…A similar result was obtained by Chen et al. (), who indicated that replacing pork fat with pre‐emulsified soybean oil increased the lightness of frankfurters. The redness values (a * ) decreased with the increasing CPOE level.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The relatively high fat content of pate products cause some negative health issues like obesity or hypertension (Lin Chen et al, 2015). Therefore reformulation of these products by fat replacers and plant origin fibers is desirable aim in the industry (Domínguez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%